2020
DOI: 10.4252/wjsc.v12.i9.952
|View full text |Cite
|
Sign up to set email alerts
|

Mechanotransduction of stem cells for tendon repair

Abstract: Tendon is a mechanosensitive tissue that transmits force from muscle to bone. Physiological loading contributes to maintaining the homeostasis and adaptation of tendon, but aberrant loading may lead to injury or failed repair. It is shown that stem cells respond to mechanical loading and play an essential role in both acute and chronic injuries, as well as in tendon repair. In the process of mechanotransduction, mechanical loading is detected by mechanosensors that regulate cell differentiation and proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 131 publications
(175 reference statements)
2
16
0
Order By: Relevance
“…Mechanical loading of tendon tissue is essential for tendon maturation during development, tendon homeostasis, and degeneration. Many reviews focus in-depth on the history of understanding matrix turnover, tendon biomechanics, and the methods/models used to understand tendon as well as ligament mechanobiology (Lavagnino et al, 2015;Thomopoulos et al, 2015;Wang and Chen, 2018;Dyment et al, 2020;Friese et al, 2020;Gracey et al, 2020;Wang et al, 2020;Bramson et al, 2021). In addition, in vivo models of tendon degeneration are the focus of another review (Theodossiou and Schiele, 2019).…”
Section: Evaluation Of Model Systemsmentioning
confidence: 99%
“…Mechanical loading of tendon tissue is essential for tendon maturation during development, tendon homeostasis, and degeneration. Many reviews focus in-depth on the history of understanding matrix turnover, tendon biomechanics, and the methods/models used to understand tendon as well as ligament mechanobiology (Lavagnino et al, 2015;Thomopoulos et al, 2015;Wang and Chen, 2018;Dyment et al, 2020;Friese et al, 2020;Gracey et al, 2020;Wang et al, 2020;Bramson et al, 2021). In addition, in vivo models of tendon degeneration are the focus of another review (Theodossiou and Schiele, 2019).…”
Section: Evaluation Of Model Systemsmentioning
confidence: 99%
“…Concerning rotator cuff repair, the scaffold is an effective tool for transmitting mechanical stimulation to delivered cells; thus, the mechanical environment provided by biomaterials should be considered in cell delivery. The mechanical stimulation of stem cells is vital in tendon tissue repair and has been shown to influence the differentiation and proliferation of stem cells ( Wang H.-N. et al, 2020 ). The magnitude of stretching could lead to different cell fates.…”
Section: Biomaterialsmentioning
confidence: 99%
“…The magnitude of stretching could lead to different cell fates. Studies indicated that 4% stretching promoted the differentiation of TPSCs into tenocytes with increased gene expression of COL1A1 ; 8% stretching, however, promoted the differentiation of TPSCs into non-tenocytes, including adipocytes, chondrocytes, and osteocytes, aside from differentiation into tenocytes, as evidenced by higher expression levels of genes such as PPARγ , COL2A1 , Sox9 , and Runx2 in vitro ( Wang H.-N. et al, 2020 ).…”
Section: Biomaterialsmentioning
confidence: 99%
“…Both acute and chronic injuries may completely or partially break tendon continuity. However, acute injuries have a higher probability of complete regeneration [ 19 , 20 ]. In turn, chronic injuries, which arise from overload and lead to tissue degeneration, are known as tendinopathies.…”
Section: Tendon Histology and Pathologymentioning
confidence: 99%